2022
DOI: 10.2142/biophysico.bppb-v19.0041
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gap junctions upon Ca<sup>2+</sup> propagation from stimulated keratinocytes to DRG neurons

Abstract: Biophysics and Physicobiologyhttps://www.jstage.jst.go.jp/browse/biophysico/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…That is, OXT may be produced in DRG neurons when the skin is gently dabbed, thereby contributing to pain relief. Our research group also confirmed that intracellular Ca 2+ propagates from peripheral keratinocytes to DRG neurons via gap junctions [15] in addition to the ATP-mediated pathway, which is generally thought to be involved in the transmission of information in keratinocytes and DRG neurons [16]. In other words, the information of the physical stimulus is transmitted from keratinocytes to DRG neurons via multiple pathways.…”
Section: Introductionsupporting
confidence: 74%
“…That is, OXT may be produced in DRG neurons when the skin is gently dabbed, thereby contributing to pain relief. Our research group also confirmed that intracellular Ca 2+ propagates from peripheral keratinocytes to DRG neurons via gap junctions [15] in addition to the ATP-mediated pathway, which is generally thought to be involved in the transmission of information in keratinocytes and DRG neurons [16]. In other words, the information of the physical stimulus is transmitted from keratinocytes to DRG neurons via multiple pathways.…”
Section: Introductionsupporting
confidence: 74%